2014
DOI: 10.1177/1074248414555403
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blockers and Hypertension

Abstract: Effective treatment of high blood pressure (BP) represents a key strategy for reducing the burden of hypertension-related cardiovascular and renal diseases. In spite of these well-established concepts, hypertension remains poorly controlled worldwide. In order to improve BP control in patients with hypertension, several interventions have been proposed, among which (1) preferred use of more effective, sustained, and well-tolerated antihypertensive drug aimed to ensure adherence to prescribed medications and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 71 publications
1
28
0
3
Order By: Relevance
“…However, several mechanisms might be involved (Godfraind, 2014). As demonstrated in various clinical trials (Tocci et al, 2015), BP lowering reduces the incidence of stroke and myocardial infarction. Head-to-head comparisons are incomplete but ASCOT trial (Sever et al, 2003) and several meta-analyses indicate that CCBs offer a better protection against stroke and myocardial infarction than angiotensin receptor blockers (Wang et al, 2007).…”
Section: Key Information About Clinical Usefulness Of Ccbsmentioning
confidence: 90%
“…However, several mechanisms might be involved (Godfraind, 2014). As demonstrated in various clinical trials (Tocci et al, 2015), BP lowering reduces the incidence of stroke and myocardial infarction. Head-to-head comparisons are incomplete but ASCOT trial (Sever et al, 2003) and several meta-analyses indicate that CCBs offer a better protection against stroke and myocardial infarction than angiotensin receptor blockers (Wang et al, 2007).…”
Section: Key Information About Clinical Usefulness Of Ccbsmentioning
confidence: 90%
“…The relationship between hypertension and intracellular calcium concentration has been confirmed by a large number of experiments [4][5][6][7]. Therefore, changes in the function of calcium channel proteins, which have a regulatory effect on intracellular calcium concentration, may be closely related to the abnormal changes in blood pressure and the development of hypertension.…”
mentioning
confidence: 96%
“…Beyond evidence in favour of cardiovascular and renal protection, clinical trials have also demonstrated a better tolerability profile and favourable metabolic properties by RAS-inhibiting drugs, especially ARBs and by CCBs compared to β-blockers and diuretics, thus promoting the use of these drug classes, both in monotherapy and in combination therapies for hypertension management and control. 12 Diabetic and black hypertensive patients with low renin levels, salt-sensitive and volume-expanded are more often responsive to a CCB than to an ACE inhibitor or a β blocker. Also, the response to increasing the dose of a CCB is generally that of significant additional BP reduction, which separates this drug class from both ACE inhibitors and ARBs.…”
mentioning
confidence: 99%
“…13 Indeed, monotherapy based on CCBs has demonstrated to provide sustained antihypertensive efficacy and to reduce cardiovascular and renal complications compared to other antihypertensive drug classes. 12 Calcium channel blockers are effective as single-drug therapy in approximately 60% of patients in all demographic groups and all grades of Hypertension. 2 However, the reduction of blood pressure associated with these agents is associated with reflex sympathetic overactivity, which leads to increased cardiovascular morbidity and mortality.…”
mentioning
confidence: 99%